Ability to Translate and Writing Skill: A Correlational Study - Moh Hanafi (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2018)
This report was a finished piece of research which was aimed to find out the correlation between students’ mastery to translate and their ability to write. It was hypothesized that the students with better mastery to translate can produce a better writing product. There were two test administered in this study. First test was translation test in which the students should translate text provided by the researcher. They should show their ability to translate from Indonesian into English. The second test was a writing test. In this test, the students should write a descriptive text. They should show how they write in acceptable English. From 24 students of the first semester of English Department STKIP PGRI Tulungagung, the coefficient of the correlation of Kendal Tau’s analysis was .552. It can be interpreted that there was a positive medium correlation between the variables. To sum it up, the translation mastery, according to this study, correlate well to the ability of writing. Students who have better mastery in writing usually have better ability to write. Therefore, we can assume that this study gives a new insight on the theories of translation mastery and writing ability.